PENGUKURAN KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN PADA INDUSTRI TEMPE MURNI MUCHLAR - , IGNATIA ANGGUN K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Customer satisfaction is one indicator of the success of the service provided by the Tempe Industrial Pure Muchlar. Service is considered satisfactory if it can meet the expectations of its customers. This study aims to analyze the influence of service quality dimensions namely reliability, responsiveness, assurance, empathy and tangible to customer satisfaction, and explain the five dimensions of service quality. This study uses descriptive analysis with a quantitative approach. Subjects were 40 people who became customers in Tempe Industrial Muchlar selected using accidental sampling method. Results of data analysis using quantitative descriptive analysis showed that of the 18 dimensions of service quality indicators used in this study, there are 17 indicators that have met the level of customer satisfaction and one indicator that has not met the level of customer satisfaction.